Pemetaan Digital Jenis Lapisan Tanah Permukaan Kota Banjarmasin - Muhammad Afief Ma’ruf; Rusliansyah Rusliansyah; Agil Arief Rachman (AGREGAT, 2021)
AbstractWith the help of GIS (Geographic Information System), information such as the results of soil testing in the field can be combined with other information such as groundwater levels, laboratory soil test results and other test results. In addition, the test location can be found in geographic coordinate format. This integrated information can be referred to as a database. Information on the results of soil testing in the field from a database can be modeled to produce a profile shape from the test result parameters such as the soil layer type profile map. This study aims to present an information system based on geographic-based soil testing data in all areas of Banjarmasin City. This research was conducted by compiling all the data from soil testing results and create a map of soil surface types along the Banjarmasin city area with the help of GIS. As many as 37 Standar Penetration Test (SPT) test points and 45 Cone Penetration Test (SPT) test points in the city of Banjarmasin are integrated with geographic information system in the form of maps of the types of soil layers on the surface of Banjarmasin City. The results of this study shows that the dominant soil layers in the surface layer in Banjarmasin City are organic clay and silty clay, which are included in the soft soil category. This means that the soil conditions of Banjarmasin City are less suitable for the application of foundation construction with shallow foundation types, because of the relatively small bearing capacity of soft soils. So that in building construction planning in Banjarmasin City, it is necessary to pay attention to the things that are challenges in construction construction on soft soils, namely the relatively small bearing capacity of the land and the relatively large land subsidence. Keywords: Geographic Information System, Journal, Soil Type, Banjarmasin City, Digital Map  AbstrakDengan bantuan GIS (Geographic Information System), informasi seperti hasil pengujian tanah di lapangan dapat dipadukan dengan informasi lainnya seperti muka air tanah, hasil pengujian tanah di laboratorium maupun hasil pengujian lainnya. Selain itu, lokasi pengujian dapat diketahui dalam format koordinat geografis. Informasi yang terpadu tersebut dapat disebut sebagai basis data. Informasi hasil pengujian tanah di lapangan dari sebuah basis data dapat dibuat model untuk menghasilkan bentuk profil dari parameter hasil pengujian seperti peta profil jenis lapisan tanah. Penelitian ini mencoba menyajikan sistem informasi dari data hasil pengujian tanah berbasis geografis di seluruh wilayah Kota Banjarmasin. Penelitian ini dilakukan dengan cara mengkompilasi seluruh data hasil pengujian tanah dan membuat peta jenis tanah permukaan di sepanjang wilayah kota Banjarmasin dengan bantuan GIS. Sebanyak 37 titik uji Standar Penetration Test (SPT) dan 45 titik uji sondir di kota Banjarmasin diintegrasikan dengan sistem informasi geografis dalam bentuk peta jenis lapisan tanah di permukaan Kota Banjarmasin. Hasil penelitian ini memberikan informasi bahwa lapisan tanah yang dominan di lapisan permukaan di Kota Banjarmasin adalah lempung organik dan lempung berlanau, yang termasuk dalam kategori tanah lunak. Ini berarti bahwa kondisi permukaan tanah Kota Banjarmasin kurang cocok untuk pengaplikasian konstruksi pondasi dengan jenis pondasi dangkal, karena daya dukung tanah lunak yang relatif kecil. Sehingga dalam perencanaan konstruksi bangunan di Kota Banjarmasin, perlu memperhatikan hal-hal yang menjadi tantangan dalam pembangunan konstruksi di tanah lunak, yaitu daya dukung tanah yang relatif kecil dan penurunan tanah yang relatif besar.